2007
DOI: 10.1097/brs.0b013e31814b2d52
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications of Lumbar Pedicle Subtraction Osteotomy

Abstract: Intraoperative or postoperative neurologic deficits are relatively common following a PSO; however, in a majority of cases, deficits are not likely to be permanent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
126
3
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(141 citation statements)
references
References 34 publications
5
126
3
7
Order By: Relevance
“…27 Buchowski et al retrospectively evaluated 108 patients who had undergone lumbar PSO and found the incidence of neurological complications, defined as the loss of bowel or bladder control only, to be 11.1%. 5 The rate of neurological complications is higher in the present study, probably because of our more comprehensive definition of neurological complications. Variation in the follow-up could also lead to differences in the rates of neurological complications between the studies.…”
Section: Discussionmentioning
confidence: 51%
“…27 Buchowski et al retrospectively evaluated 108 patients who had undergone lumbar PSO and found the incidence of neurological complications, defined as the loss of bowel or bladder control only, to be 11.1%. 5 The rate of neurological complications is higher in the present study, probably because of our more comprehensive definition of neurological complications. Variation in the follow-up could also lead to differences in the rates of neurological complications between the studies.…”
Section: Discussionmentioning
confidence: 51%
“…However, there is a paucity of current peer-reviewed literature addressing the premise that adult spinal deformity patients benefit from surgical treatment [2][3][4]. Yadla et al [8] in a recent systematic review analysed 49 articles reporting data in 3,299 patients, and found only four articles reporting on all specified outcome measures (change in ODI scores before and after surgery, change in SRS scores, curve reduction, complications, and pseudoarthrosis) [9][10][11][12]. The articles analysed reported a huge number of complications, with a pooled incidence of 41.2 % [8].…”
Section: Discussionmentioning
confidence: 99%
“…They believed that PSO may achieve a larger correction, with shorter operative time and less blood loss compared with anteriorposterior surgery. Buchowski et al, 3 showed an intraoperative or post-operative neurological deficit rate of 11.1 % (12 of 108 patients), but only 2.8 % of deficits were permanent over a 10-year period. Deficits were always unilateral and were not detected by neuromonitoring.…”
Section: Discussionmentioning
confidence: 99%